Educational Class Program Effectively Improves Adolescents’ Knowledge on Hypertension - Maisa, Benny Alexander; Taufiqa, Zuhrah; Lisrha, Nayla; Volasoohy, Navila Samsa (Media Karya Kesehatan, 2025)
The prevalence of hypertension among adolescents continues to rise both nationally and globally. Hypertension at a young age often goes undetected and carries the risk of leading to serious complications later in life, including cardiovascular disease, stroke, kidney failure, and even death. The lack of adolescent knowledge regarding risk factors, symptoms, prevention, and the long-term impact of hypertension remains a major barrier to effective health promotion and prevention efforts. This activity aimed to enhance adolescent knowledge of hypertension—its definition, risk factors, symptoms, prevention, and management—through a structured, interactive educational class program. The program was implemented on three main stages: preparation, implementation (including material presentation and discussion), and evaluation through pre- and post-tests to a total of 29 student representatives from schools and universities in Padang City, with an average age of 18 years, participated. The results showed a significant increase in knowledge scores (p < 0.001), with mean pre-test and post-test scores of 15.04 ± 2.6 and 18.52 ± 0.94, respectively (Δ = 3.48). Significant improvements were observed in general knowledge of hypertension, risk factors, symptoms and consequences, dietary prevention strategies, and hypertension management (p < 0.01). These findings indicate that the educational class program was effective in improving adolescent health literacy regarding hypertension. It is recommended that this health education intervention be expanded to strengthen hypertension prevention efforts among young age groups. Keywords: Adolescent hypertension, educational class program, prevention, healthy behavior.